(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Mental health and well-being are crucial aspects of our overall health. They encompass emotional, psychological, and social well-being, affecting how we think, feel, and act. Understanding and improving our mental health can lead to a more balanced, fulfilling life.